A socioeconomic assessment of artisanal cocoa processing and commercialization in the Center and South regions of Cameroon: Challenges and prospects - Nyambi, G. N.; Maba, G.; Ngang, Nso A.; Mveme, M.; Simo, B.; Nossi, E. J.; Sidonie, N.; Okolle, N. J. (European Journal of Applied Sciences, 2021)
Artisanal cocoa processing is a major source of income in the cocoa producing hubs of the Center and South regions of Cameroon. A socioeconomic assessment of artisanal cocoa processing and commercialization among smallholder farmers in the Center and South regions of Cameroon was conducted. The study described the socio-demographic characteristics of the cocoa processors in the study site; examined the situation and trends in the production of processed cocoa products; described the marketing methods and economic benefits of the activity; identified constraints and mitigation strategies for the growth and expansion of cocoa processing; opportunities relating to further development and growth of cocoa processing and finally the organizational and institutional linkages involved in the activity. Data was collected in three phases involving literature review, discussions with regional authorities of the Ministry of Scientific Research and Innovation, the Ministry of Agriculture and Rural Development, and focus group discussions with direct stakeholders in the cocoa value chain. Structured questionnaires were administered to 105 cocoa processors to address the specific objectives of the study. Descriptive and inferential analysis revealed that 87.62 % of the processors were females with 77.4 % being married. 93.33% of processors had received training for processing activities. The majority of respondents (61.9%) processed less than 50kg of cocoa beans which is auto-consumed. Just 2.9 percent processed up to 2000kg cocoa beans per annum. All-in cooperative processors, partial cooperative processors, and individual processors are social organizational types in the processing sector. Individual processors were predominant in the Center region. Eleven different products are processed from cocoa beans in the two regions of the study. Cocoa butter is indicated as the most consumed, expensive, and difficult product to process. The mean income earnings for the Center and South regions were 102,466 FRSCFA and 111,000 FRSCFA, respectively. Implicated stakeholders include cocoa farmers, Cameroon cocoa service, and Cameroon development society, license buying companies, cocoa processing companies, civil society and line ministries that play specific roles in the processing value chain. Lack of adequate processing and conservation equipment, storage facilities, and knowledge on conservation and storage techniques were indicated as difficulties in the processing activity. The study population tends to lean on cocoa natural products for healthcare. Efficient functional platforms would enhance the marketing of processed cocoa products. Government support and investment in cocoa processing would promote the sustainability of the artisanal processing value chain. Complementary policy actions and investment from the government are necessary for the success and sustainability of these innovations.